Sphenopalatine artery rupture following posterior nasal nerve cryoablation: a rare but serious delayed complication - Zhorov, Iris; Goldstein, Melissa; Carniol, Eric (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2026)
Posterior nasal nerve (PNN) cryoablation is an emerging minimally invasive procedure for managing refractory chronic rhinitis. Although generally well-tolerated, complications can occur. This report presents the first documented case of sphenopalatine artery (SPA) rupture following PNN cryoablation, highlighting the need for vigilance in postoperative care. A 64-year-old female developed delayed epistaxis one month postoperatively, requiring emergent arterial ligation. This case underscores the importance of anatomical considerations, and the potential risks associated with this innovative treatment.